Early sport specialization and long-term throwing arm health in college baseball players - Wilkins, S. J.; Bell, D. R.; Kahanov, L.; Martin, M.; Post, E. G. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Early sport specialization is associated with increased risk of overuse injuries in several sports, including baseball. However, limited evidence exists evaluating how early sport specialization affects patient-reported outcome measures as they age. The purpose of this study was to determine differences in Kerlan-Jobe Orthopedic Clinic (KJOC) Shoulder and Elbow Scores among collegiate baseball players based on the grade when a participant first reported high specialization behaviors.